The Impact of the National Minimum Wage on Labour Productivity in Britain - Richard Croucher; Marian Rizov (E-Journal of International and Comparative Labour Studies, 2012)
In this paper we explore the link between firm labour productivity and the introduction of the NMW over a more than ten-year span covering longer periods before and after the NMW introduction. We use the FAME dataset which contains firm level micro data to calculate firm-specific labour productivity measures and then aggregate them to the level of the low-paying sectors as identified by the Low Pay Commission (LPC). These include several service industries, agriculture and food processing, textiles and clothing manufacturing. Our results from difference-in-differences analysis show that, with notable exceptions, aggregate LPC sector labour productivity has been significantly positively affected by the NMW in the long run; the effects' magnitudes vary by sector. In most of the sectors the impact is statistically significant and positive with the exception of hairdressing, leisure and agriculture where the impact is positive but not statistically significant. We also analyse labour productivity by firm-size groups, according to the LPC classification and find substantial heterogeneity in responses to the NMW over time as the increases in productivity are more marked in larger firms.
Keywords: J08; J31; J38; 330; Minimum wage; Low-pay sectors; Productivity; UK